Herpes Simplex Virus Type 2 Infection-Induced Expression of CXCR3 Ligands Promotes CD4+ T Cell Migration and Is Regulated by the Viral Immediate-Early Protein ICP4 - Zhang, Mudan; Deng, Xu; Guan, Xinmeng; Geng, Lanlan; Fu, Ming; Zhang, Binman; Chen, Rui; Hu, Huimin; Hu, Kai; Zhang, Di; Li, Mei; Liu, Yalan; et al. (Frontiers in Immunology, 2018)
HSV-2 infection-induced CXCR3 ligands are important for the recruitment of virus-specific CD8+ T cells, but their impact on CD4+ T cell trafficking remains to be further determined. Given that recruitment of CD4+ T cells to infection areas may be one of the mechanisms that account for HSV-2 infection-mediated enhancement of HIV-1 sexual transmission, here we investigated the functionality of HSV-2 infection-induced CXCR3 ligands CXCL9, CXCL10 and CXCL11 in vivo and in vitro, and determined the viral components responsive for such induction and the underlying mechanisms. We first found that the expression of CXCR3 ligands CXCL9, CXCL10 and CXCL11 was increased in mice following vaginal challenge with HSV-2, while CXCL9 played a predominant role in the recruitment of CD4+ T cells to the vaginal foci of infected mice. HSV-2 infection also induced the production of CXCL9, CXCL10 and CXCL11 in human cervical epithelial cells. Of note, although HSV-2 induced the expression of all the three CXCR3 ligands, the induced CXCL9 appeared to play a predominant role in promoting CD4+ T cell migration, reflecting that the concentrations of CXCL10 and CXCL11 required for CD4+ T cell migration are higher than that of CXCL9. We further revealed that, ICP4, an immediate-early protein of HSV-2, is crucial in promoting CXCR3 ligand expression through the activation of p38 MAPK pathway. Mechanistically, ICP4 binds to corresponding promoters of CXCR3 ligands via interacting with the TATA binding protein (TBP), resulting in the transcriptional activation of the corresponding promoters. Taken together, our study highlights HSV-2 ICP4 as a vital viral protein in promoting CXCR3 ligand expression and CXCL9 as the key induced chemokine in mediating CD4+ T cell migration. Findings in this study have shed light on HSV-2 induced leukocyte recruitment which may be important for understanding HSV-2 infection-enhanced HIV-1 sexual transmission and the development of intervention strategies.